Extracorporeally irradiated autografts in pelvic reconstruction after malignant tumour resection - Sys, Gwen (Springer-Verlag, 2002)
We treated 15 patients suffering from an extracompartmental malignant pelvic tumour by resecting the affected part of the bone, irradiating it extracorporeally with 300 Gy, and reimplanting it after having removed the bulk of the lesion. Adjuvant therapies were used according to the type and extension of the tumour. Follow-up was an average of 4 years 6 months. Complications were seen in 13 patients. Most mechanical complications were related to the use of hip arthroplasties. Internal fixation of the graft failed in one case only, infection was seen in three cases, and seven patients died after local recurrence. Functional scores were fair. Although many complications were seen, this method remains our treatment of choice.